Desain dan Analisa Electrical Submersible Pump Pada Lapangan P-N 62 Sebagai Upaya Peningkatan Produksi - Lestari, Nila Khoirul Tria; Abror, Hadziqul (Petroleum Engineering, Faculty of Engineering, University of Jember, 2024)
The reservoir pressure in the P-N oil well is currently showing a significant decline. Some oil wells cannot flow naturally, so artificial lift is required to maintain Jabung oil production and deplete the remaining oil reserves. Analysis and evaluation of the use of artificial lift electrical submersible pump (ESP) in the P-N62 well using calculation and simulation to see the production performance of a well after adding artificial lift based on the results of the calculation it is determined that the ESP TD800 Series-400 with 117 stages with the ability to produce up to 990.96 BFPD and has an efficiency of 58.67% which will be used to increase the production rate at the P-N62 well. Keywords: artificial lift; electrical submersible pump (ESP); Inflow Performance Relationship; petroleum